Communication and Service Quality in Public Sector: an Ethnographic Study of a State Court of Justice in Jakarta - Widodo, Aan; Rahmat Hidayat, Dadang; Venus, Anter; Suseno, Sigid (International Journal of Engineering and Technology, 2018)
The purpose of this study is to describe the ethnography of a district court in Jakarta in terms of communication and service quality. This study was conducted to answer two basic questions: how is communication applied in a district court and how is the quality of service in a district court in Jakarta. This research uses qualitative method with ethnographical approach. Researchers conduct in-depth interviews, participant observation, and documents. The results of this study indicate that the communication and quality of services implemented do not meet the Minimum Standards of Judicial Services.Â Â